UMKM Study Pendahuluan Untuk Melihat Kemampuan Pemasaran Dari Bisnis Telur Puyuh Dalam Menhadapi Kompetitor (Studi Kasus Pada CV Jayanti Utama Peternak Burung Puyuh Bogor) - Nashar, Muh; Wahyuningsih, Diah (LPPM Institut Bisnis dan Informatika Kesatuan, 2016)
The implementation of ASEAN Economic Community 2015 is become high challenge for Indonesian SME’s as the economic will be more competitive. There are four main problem for Indonesia SME namely financing, management, marketing and regulation. Marketing is one of the main problem for SME to be survive on this business. This paper describe the current conditions on CV Jayanti Utama on facing competitors. With using qualitative method this paper describe on the problem on marketing quail eggs business in Bogor Area. The demand of quail eggs is very high around 12,5 million eggs per week and the farmers can only fulfills 10 percent for this demands. The company has not used this market opportunity as result of lack skill and knowledge.